Relationship between BUN/Cr and Prognosis of HF Across the Full Spectrum of Ejection Fraction - Kang, Yuan; Wang, Conglin; Niu, Xiaojing; Shi, Zhijing; Li, Mingxue; Tian, Jianli (Arquivos brasileiros de cardiologia, 2023)
In patients with heart failure (HF), due to the relative deficiency of blood volume, neurohormone system activation leads to renal vasoconstriction, which affects the content of blood urea nitrogen (BUN) and creatinine (Cr) in the body, while BUN and Cr are easily affected by other factors. Therefore, BUN/Cr can be used as another marker for the prognosis of HF. Explore the prognosis of adverse outcome of HF in the high BUN/Cr group compared with the low BUN/Cr group across the full spectrum of ejection fraction. From 2014 to 2016, symptomatic hospitalized HF patients were recruited and followed up to observe adverse cardiovascular outcomes. Logistic analysis and COX analysis were performed to determine significance. p-values <0.05 were considered statistically significant. In the univariate logistic regression analysis, the high BUN/Cr group had a higher risk of adverse outcome in heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF). Multivariate logistic regression analysis showed that the risk of cardiac death in the HFrEF group was higher than that in the low BUN/Cr group, while the risk of all-cause death was significant only in 3 months (p<0.05) (Central Illustration). The risk of all-cause death in the high BUN/Cr in the HFpEF group was significantly higher than that in the low BUN/Cr group at two years. The high BUN/Cr group is related to the risk of poor prognosis of HFpEF, and is not lower than the predictive value of left ventricular ejection fraction (LVEF).